Animal babies - Hamsa, Bobbie; Dunnington, Tom (Danbury, Conn. : Childrens Press, 1985)
Provides drawings and names of baby animals, including a kitten, a fawn, a piglet, and a lamb.
"Level B, early fluent"--Cover p. [4].
Includes a word list.
1.0
K-3
P-2.
Keywords: Animals -- Infancy -- Juvenile literature; Animals -- Infancy; Animal babies; Readers (Elementary).